Regulatory Deficiencies in Investor Protection on the CFD Market in Poland - Jarosz, Wojciech; Górny, Mikołaj (Journal of Finance and Financial Law, 2025)
The purpose of the article. Retail investors in capital markets have enhanced accessibility to a broad spectrum of financial instruments via online trading platforms operated by investment firms. However, these instruments are inherently complex and high-risk, making independent analysis and informed decision-making particularly challenging for non-professional investors. Leveraged products amplify both gains and losses, posing heightened risks in volatile markets like cryptocurrencies. This article critically examines the limitations of the current regulatory framework governing contracts for difference (CFDs) in Poland, following regulations introduced (Decision No. DAS.456.2.2019) by the Polish Financial Supervision Authority (KNF). This decision established restrictions on the offering, distribution, and sale of CFDs to retail clients. Methodology. This study adopts a regulatory and market analysis approach to identify critical deficiencies and challenges in investor protection within the Polish CFD market. It relies on a review of legal frameworks, supervisory reports, and publicly available data from CFD brokers. Key areas of analysis include supervisory reports from the KNF, assessment of risk disclosures, examination of brokerage models, evaluation of cross-border activities, and review of marketing strategies. Results of the research. The analysis highlights persistent issues such as the circumvention of restrictions by cross-border brokers, the continued use of aggressive marketing strategies, and unresolved conflicts of interest within brokerage models. By reviewing legal frameworks, reports, and CFD broker data highlights regulatory shortcomings in investor protection. The findings suggest that while regulatory interventions have introduced certain protective measures, significant loopholes allow brokers to maintain high-risk practices. The article calls for enhanced regulatory oversight and provides recommendations for strengthening investor protection in the Polish financial market.